FAKTOR-FAKTOR RESIKO LINGKUNGAN DAN PERILAKU YANG MEMPENGARUHI KEJADIAN KESAKITAN MALARIA DI PROPINSI SUMATERA SELATAN ANALISIS LANJUT DATA RISET KESEHATAN DASAR 2007 - Saikhu, Akhmad; Budianto, Anif; Yuliani, Rosda Cita (Publikasi Penelitian Terapan dan Kebijakan, 2009)
Malaria is a major public health problem in Indonesia, causing mortality not only for infant and pregnant women but also decreasing productifity among workers. To provide important and up to date of health related information, National Health Institute Research and Development – MOHRepublic Indonesia had held National Baseline Health Research (NBHR) on 2007. The extended analisis of NHBR particularly on malaria has been conducted to evaluate distribution of case malaria and its influencing risk factors especially the behavioral and environmental factor. This study found that there were associations between malaria cases with age (p<0.000), occupation (p<0.005), time consumed to seek health services (posyandu), health services utilization (p<0.05), type of water sludge irrigation (p<0.001) and usage of insecticide mosquito bed net (p<0.000). This study recommended the improvement environment condition and health education to improve knowledge, attitude and practice, provide more and better insecticide mosquito bed net can be applied to solve the problems that were issued from the findings of the study. Extended malariaresearch should be conducted to provide better understanding of malaria control.